How Cooperative Governance Improves Quality Consistency in Patchouli Essential Oil Value Chains - Mochammad Rafli Naseery; Pramesti Salsabil Putri Herjuno; Zainur Rijal; Ario S. Setiadi (Husnayain Business Review, 2026)
Quality inconsistency remains a persistent challenge in smallholder-based patchouli essential oil value chains, where fragmented production systems and weak coordination limit compliance with market quality standards. This study examines how cooperative governance improves quality consistency by functioning as a coordination authority within a quality-sensitive agricultural value chain. Using a qualitative case study of a patchouli essential oil cooperative in Legok, Indonesia, data were collected through field observations, semi-structured interviews with cooperative managers, member farmers, and downstream buyers, as well as document analysis. The findings reveal that cooperative governance enhances quality consistency by centralizing production standards, coordinating harvesting and distillation processes, and embedding traceability as an internal governance mechanism rather than a standalone technological tool. This governance arrangement reduces quality variability, strengthens accountability among value chain actors, and improves the cooperative’s bargaining position in downstream markets. The study contributes to agribusiness and value chain governance literature by demonstrating that quality upgrading in smallholder systems is primarily driven by governance reconfiguration rather than technical interventions alone, offering practical implications for cooperative management and policy design in quality-sensitive agricultural markets.